An organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, and its preparation method and application

The organic crystal-changing agent with carboxyl and thiol groups controls α-hemihydrate gypsum growth, providing high-purity, stable short columnar crystals with improved mechanical properties, addressing impurity and cost issues in existing methods.

CN118561310BActive Publication Date: 2024-12-27WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410629539.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2024-12-27
Estimated Expiration
2044-05-21

AI Technical Summary

Technical Problem

Existing methods for preparing α-hemihydrate gypsum using citric acid as a crystal-transforming agent introduce impurities, affect crystal growth, and increase production costs due to complex processes, while composite agents can alter crystal structure and stability.

Method used

An organic crystal-changing agent with multiple carboxyl and thiol functional groups is used to form complexes with calcium ions, controlling crystal growth direction, resulting in high-purity, stable short columnar α-hemihydrate gypsum with improved mechanical properties.

Benefits of technology

The organic agent achieves regular and stable short columnar crystals with enhanced mechanical properties and efficiency, overcoming impurity issues and cost concerns of previous methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118561310B_ABST
    Figure CN118561310B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of α-hemihydrate gypsum production, and in particular to an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, and a preparation method and application thereof, wherein compound A and compound B are dissolved in an organic solvent, heated to 45-85° C. under nitrogen protection, compound C is added, and the reaction is continued for 2-4 hours to obtain an organic crystal-changing agent, which is used for the preparation of α-hemihydrate gypsum. The present invention contains multiple carboxyl and sulfhydryl functional groups in an organic crystal-changing agent, which can form a complex with metal ions, and can be combined with metal ions through coordination, thereby reducing the generation of α-hemihydrate gypsum crystal defects, thereby obtaining a regular and stable crystal structure; by adjusting the pH value of the crystal-changing agent solution, the amount of the organic crystal-changing agent added, the reaction temperature, etc., columnar α-hemihydrate gypsum can be prepared, and the compression and flexural properties of the α-hemihydrate gypsum can be significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-strength alpha-hemihydrate gypsum production, and in particular to an organic crystal-changing agent used for preparing alpha-hemihydrate gypsum from phosphogypsum, and a preparation method and application thereof. Background Art

[0002] α-Hemihydrate gypsum is an important mineral material with a wide range of applications, including building materials, ceramic industry, medicine, etc. Its crystal structure has an important influence on its properties and uses, so it is of great significance to study its crystal form and preparation method. The crystal forms of α-hemihydrate gypsum mainly include columnar α-hemihydrate gypsum and needle-shaped α-hemihydrate gypsum. Columnar α-hemihydrate gypsum has a long columnar crystal structure, and the crystal shape presents a regular columnar shape. It has a high degree of crystallinity and crystal size, and is often used in building materials and ceramic industries; needle-shaped α-hemihydrate gypsum has a slender needle-shaped crystal structure, and the crystal size is small, and it is often used in the medical field.

[0003] When preparing columnar α-hemihydrate gypsum, a normal pressure salt solution method or a hydrothermal method is usually used. During the preparation process, the morphology and quality of the crystals are affected by many factors, including reaction conditions, selection of a crystal-transforming agent, and crystal growth rate. Chinese patent CN110818304B discloses a method for preparing α-hemihydrate gypsum, which uses citric acid as a crystal-transforming agent to prepare dihydrate gypsum, and then crystal-transforms the dihydrate gypsum under the stimulation of α-hemihydrate gypsum seeds to obtain α-hemihydrate gypsum. However, using citric acid as a crystal-transforming agent may introduce impurities and affect the purity of the crystals; at the same time, citric acid has a certain effect on the growth rate of the crystals, resulting in uneven crystal growth or abnormal growth, which in turn affects the quality and performance of the α-hemihydrate gypsum. Chinese patent CN114890697B discloses a composite crystal-changing agent for gypsum and its application in the preparation of α-hemihydrate gypsum, wherein the composite crystal-changing agent for gypsum comprises component A and component B; the component A is at least one of C1-C10 carboxylic acids and their derived salts, anhydrides and amides; the component B is at least one of perylene cyclocarboxylic acids and their derived salts, anhydrides and amides. The combination of components A and B in the composite crystal-changing agent can achieve synergy, and can effectively induce red, high-strength, low-standard-consistency water consumption, short-columnar, high-purity, stable structure and uniform particles of α-hemihydrate gypsum. However, the preparation process of the composite crystal-changing agent is relatively complicated, which increases the production cost of the crystal-changing agent, thereby increasing the preparation cost of α-hemihydrate gypsum; at the same time, the effects of components A and B may cause changes in the crystal structure, affecting the stability of the α-hemihydrate gypsum crystal form, and thus affecting its performance. Summary of the invention

[0004] To solve the above problems, the present invention proposes an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, and a preparation method and application thereof, which can obtain short columnar α-hemihydrate gypsum crystals with high purity, stable crystal form and uniform distribution, and at the same time can improve the mechanical properties of the prepared α-hemihydrate gypsum.

[0005] The technical solution of the present invention is achieved in this way:

[0006] In a first aspect, the present invention provides an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, and the molecular structure of the organic crystal-changing agent is as follows:

[0007] The organic crystal-changing agent is used for the preparation of alpha-hemihydrate gypsum.

[0008] In a second aspect, the present invention provides a method for preparing an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, comprising the following steps:

[0009] Dissolve compound A and compound B in an organic solvent, heat to 45-85°C under nitrogen protection, add compound C, and continue the reaction for 2-4 hours to obtain an organic crystal conversion agent;

[0010] Among them, the molecular structure of compound A is shown below:

[0011]

[0012] The molecular structure of compound B is shown below:

[0013]

[0014] The molecular structure of compound C is shown below:

[0015]

[0016] On the basis of the above technical solution, preferably, the molar ratio of compound A, compound B and compound C is 1:(1-5):(0.01-0.09).

[0017] On the basis of the above technical scheme, preferably, it also includes post-treatment, after the reaction is completed, the organic solvent is evaporated, ethyl acetate is added to dissolve, the layers are washed with water, and the layers are concentrated to obtain the organic crystal-transforming agent.

[0018] In the third aspect, the present invention provides an application of an organic crystal-changing agent, wherein the organic crystal-changing agent as described above or the organic crystal-changing agent prepared by the preparation method as described in any of the above items is used for the preparation of α-hemihydrate gypsum, and the preparation method comprises the following steps: adding the crystal-changing agent solution into a reactor, adding purified phosphogypsum slurry, stirring and heating to 120-140°C, filling with nitrogen until the air pressure in the reactor is 0.2MPa, reacting for 15-30min, and after the reaction is completed, filtering and washing to obtain α-hemihydrate gypsum.

[0019] On the basis of the above technical solution, preferably, the solid-liquid ratio of the purified phosphogypsum slurry is 1:(1-3)

[0020] On the basis of the above technical solution, preferably, the crystal-changing agent solution includes an organic crystal-changing agent, and the added amount of the organic crystal-changing agent is 0.08% to 0.2% of the mass of the phosphogypsum.

[0021] On the basis of the above technical solution, preferably, the pH value of the crystal transformation agent solution is 5-9.

[0022] On the basis of the above technical solution, preferably, the crystal form of the α-hemihydrate gypsum is short columnar, and the aspect ratio is about (1.5-2.2):1.

[0023] The organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum of the present invention and its preparation method and application have the following beneficial effects compared with the prior art:

[0024] (1) The organic crystal-transforming agent contains multiple carboxyl and thiol functional groups, which can form complexes with calcium ions on the two surfaces of hemihydrate gypsum along the C-axis direction, and combine with metal ions through coordination to cover the two surfaces of the C-axis, thereby slowing down the growth along the C-axis direction, thereby obtaining a regular and stable short columnar crystal structure, and the optimal aspect ratio of α-hemihydrate gypsum can reach 1.5:1;

[0025] (2) By adjusting the pH value of the crystal-changing agent solution, the amount of the organic crystal-changing agent added, the reaction temperature, etc., columnar α-hemihydrate gypsum can be prepared, and the compression and flexural properties of the α-hemihydrate gypsum can be significantly improved;

[0026] (3) The organic crystal-transforming agent provided by the present invention contains multiple carboxyl pairs, which can significantly improve the crystal-transforming efficiency. When applied to the preparation of α-hemihydrate gypsum, the crystal-transforming preparation can be achieved within 15-30 minutes, and the mechanical properties of the α-hemihydrate gypsum product can also be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 This is a Raman spectrum of the organic crystal-changing agent prepared in Example 1 of the present invention;

[0029] Figure 2 This is an electron microscope image of α-hemihydrate gypsum prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the first aspect, the present invention provides an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, wherein the high-efficiency α-hemihydrate gypsum crystal-changing agent is an organic crystal-changing agent, and the molecular structure of the organic crystal-changing agent is as follows:

[0032] The organic crystal-changing agent is used for the preparation of alpha-hemihydrate gypsum.

[0033] The organic crystal-transforming agent provided by the present invention contains multiple carboxyl and thiol functional groups. These functional groups can form complexes with calcium ions on the two faces of hemihydrate gypsum along the C-axis direction, and combine with metal ions through coordination to cover the two faces of the C-axis, thereby slowing down the growth along the C-axis direction, thereby obtaining a regular and stable short columnar crystal structure. Specifically, the organic crystal-transforming agent provided by the present invention contains eight carboxyl groups, which provide more active sites and can be combined with more Ca ions. 2+ions form complexes, thereby greatly enhancing the adsorption on the (114) surface of the α-HH crystal. This strong adsorption helps to form a more compact network film structure, effectively hindering the growth of the crystal along the c-axis direction; the eight carboxylic acid groups can form a stronger synergistic effect, which can further improve the overall performance of the crystal-transforming agent, more effectively affect the growth direction and morphology of the crystal, and help to achieve precise control of short columnar α-HH crystals. The thiol group can synergize with the carboxyl group to enhance the adsorption effect, promote the organic crystal-transforming agent to be more tightly adsorbed on the crystal surface, and slow down the growth along the C-axis direction; at the same time, the thiol group can form a coordination bond with the calcium ion through its sulfur atom, thereby forming a stable complex structure. The formation of this complex helps the interaction between the organic crystal-transforming agent and the calcium ion on the crystal surface, thereby affecting the direction and rate of crystal growth.

[0034] In a second aspect, the present invention provides a method for preparing an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, comprising the following steps:

[0035] Dissolve compound A and compound B in an organic solvent, heat to 45-85°C under nitrogen protection, add compound C, and continue the reaction for 2-4 hours to obtain an organic crystal conversion agent;

[0036] Among them, the molecular structure of compound A is shown below:

[0037]

[0038] The molecular structure of compound B is shown below:

[0039]

[0040] The molecular structure of compound C is shown below:

[0041]

[0042] On the basis of the above technical solution, preferably, the molar ratio of compound A, compound B and compound C is 1:(1-5):(0.01-0.09).

[0043] On the basis of the above technical scheme, preferably, it also includes post-treatment, after the reaction is completed, the organic solvent is evaporated, ethyl acetate is added to dissolve, the layers are washed with water, and the layers are concentrated to obtain the organic crystal-transforming agent.

[0044] In the above reaction, compound A provides a thiol group of the chain transfer functional group, compound B has a hydrophilic functional group, and compound C, as an initiator, decomposes in a nitrogen atmosphere at 45 to 85°C to generate free radicals. Compound A and compound B undergo an addition reaction under the initiation of compound C to obtain an organic crystal-transforming agent. Specifically, compound C is cracked under the action of heat to generate azo radicals. These azo radicals have strong activity and will react with the molecules of compound A and compound B in the reactants. For example, azo radicals may react with the thiol group in compound A to form free radical intermediates; these free radical intermediates will continue to participate in the reaction and undergo further free radical polymerization reaction with compound B to eventually form an organic crystal-transforming agent.

[0045] In the third aspect, the present invention provides an application of an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, wherein the organic crystal-changing agent is used for the preparation of α-hemihydrate gypsum, and the preparation method comprises the following steps: adding a crystal-changing agent solution into a reactor, adding purified phosphogypsum slurry, stirring and heating to 120-140°C, charging nitrogen until the pressure in the reactor is 0.2MPa, reacting for 15-30 minutes, and after the reaction is completed, filtering and washing to obtain α-hemihydrate gypsum. The organic crystal-changing agent provided by the present invention contains multiple carboxyl pairs, which can significantly improve the crystal-changing efficiency. When applied to the preparation of α-hemihydrate gypsum, the crystal-changing preparation can be achieved within 15-30 minutes.

[0046] Specifically, the purified phosphogypsum slurry refers to the phosphogypsum obtained after purification treatment and water mixed in a certain proportion, wherein the purification treatment method includes washing, neutralization flocculation, filtration, etc., the purpose of which is to remove impurities in the phosphogypsum. The pretreatment of phosphogypsum is mainly to reduce the impurity content in the phosphogypsum. The specific phosphogypsum purification treatment compliance standard is determined according to the "Pollution Control Standard for Comprehensive Utilization of Phosphogypsum" (GB25032-2010) and "Purification of Phosphogypsum by Wet-process Phosphoric Acid" (HG / T3593-2012) and other standards. The present invention does not specifically limit the pretreatment method here.

[0047] On the basis of the above technical solution, preferably, the crystal-changing agent solution includes an organic crystal-changing agent, and the amount of the organic crystal-changing agent added is 0.08% to 0.2% of the mass of the phosphogypsum. The solid-liquid ratio of the purified phosphogypsum slurry is 1:(1 to 3).

[0048] An appropriate amount of organic crystal-transforming agent helps to form a stable crystal structure and improve the stability and deformation resistance of the crystal. If the amount of organic crystal-transforming agent added is too high, it may cause the crystal surface to be over-covered or unevenly covered, hindering the growth of the crystal; if the amount of organic crystal-transforming agent added is insufficient, it may not be able to effectively cover the crystal surface, and thus fail to form a stable complex structure, resulting in insufficient adsorption effect, leading to uncontrolled crystal growth direction and irregular morphology.

[0049] On the basis of the above technical solution, preferably, the pH value of the crystal transformation agent solution is 5-9.

[0050] The pH value of the crystal-transforming agent solution can affect the morphology and size of the crystals. An appropriate pH value can promote the orderly growth of crystals and obtain a regular crystal morphology; while a pH value that is too high or too low may cause irregular crystal morphology or hindered crystal growth. An appropriate pH value helps maintain the stability of the solution and prevents the crystals from dissolving or aggregating during the growth process, thereby ensuring the growth quality and stability of the crystals.

[0051] On the basis of the above technical solution, preferably, the crystal form of the α-hemihydrate gypsum is short columnar, and the aspect ratio is (1.5-2.2):1.

[0052] The principles and features of the present invention are further described below in conjunction with embodiments. The embodiments are only used to explain the present invention and are not used to limit the scope of the present invention.

[0053] Example 1

[0054] This embodiment provides an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum and a preparation method thereof, which specifically comprises the following steps:

[0055]

[0056] Weigh 58.56g (0.12mol) of compound A and 57.0g (0.492mol) of compound B and dissolve them in 150ml of ethanol. Heat the reaction mixture to 70°C under a nitrogen atmosphere and add 2g (0.0078mol) of compound C. Then react for 3 hours at 70°C under a nitrogen atmosphere. After the reaction is completed, evaporate part of the solvent ethanol, add 250ml of ethyl acetate to dissolve, wash three times with 100ml of water, let stand and separate, and concentrate to obtain 114.2g of a light yellow viscous oil, which is an organic crystal-transforming agent.

[0057] It should be noted that in this embodiment, the molar ratio of compound A, compound B and compound C is 1:4.1:0.065, but the molar ratio of compound A, compound B and compound C is 1:(1-5):(0.01-0.09), the heating temperature is 45-85°C, and the reaction time is 2-4h. Single adjustments within the above range or multiple combined adjustments are all within the protection scope of this embodiment.

[0058] Figure 1 The Raman spectrum of the organic crystal-changing agent prepared in this example is shown, wherein 2941 and 2678 are methylene absorption peaks; 1727 is the carbonyl absorption peak; 1460 and 1422 are CO and CS absorption peaks.

[0059] Example 2

[0060] This embodiment provides an application of an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, which specifically includes the following steps:

[0061] Weigh 0.8g of organic crystal-changing agent (the mass of organic crystal-changing agent accounts for 0.08% of the mass of phosphogypsum), add 125ml of deionized water, stir evenly, and use sodium hydroxide solution to calibrate the pH of the crystal-changing agent solution to 5. Add the crystal-changing agent solution to the reactor, turn on the agitator and adjust the speed to 300RPM, add purified phosphogypsum slurry (solid-liquid ratio is 1:1, that is, the ratio of purified phosphogypsum to water is 1:1, of which gypsum 1kg, water added is 1L), tighten the screws to seal the reactor, keep stirring and continue to heat to 120°C, connect the nitrogen bottle, fill with nitrogen until the pressure in the reactor is 0.2MPa, start the reaction, and the reaction time is 20min. After the reaction is completed, filter, wash with hot water several times, and then wash with anhydrous ethanol. The total washing time shall not exceed 5 minutes. Dry to constant weight in a vacuum oven at 110°C.

[0062] It should be noted that the reaction time is 0.5 to 3 hours, and a single adjustment or a combination of multiple adjustment methods within the above range are all within the protection scope of this embodiment.

[0063] Embodiments 3 to 11

[0064] Examples 3 to 11 provide an application of an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum. The specific operation steps are the same as those of Example 2, and the differences are shown in Table 1:

[0065] Table 1

[0066]

[0067]

[0068] It should be noted that a single adjustment or a combination of multiple adjustment methods within the above range are all within the protection scope of this embodiment.

[0069] Example 12

[0070] This embodiment provides an application of an organic crystal-changing agent for preparing α-hemihydrate gypsum from phosphogypsum, which specifically includes the following steps:

[0071] (1) Weigh 0.20g of organic crystal-changing agent, add 100ml of deionized water, stir evenly, and adjust the pH of the crystal-changing agent solution to 9.00 using sodium hydroxide solution. Add the crystal-changing agent solution to the reactor, turn on the agitator and adjust the speed to 300RPM, add purified phosphogypsum, tighten the screws to seal the reactor, keep stirring and continue to heat to 120°C, connect the nitrogen bottle, fill with nitrogen until the pressure in the reactor is 0.2MPa, start the reaction, and the reaction time is 15min;

[0072] (2) After the reaction is completed, filter, wash with hot water several times, and then wash with anhydrous ethanol. The total washing time should not exceed 5 minutes. Dry in a vacuum oven at 110°C to constant weight.

[0073] Performance Testing

[0074] After drying the α-hemihydrate gypsum prepared in Examples 2 to 12 and Comparative Example 1, samples were taken, diluted with anhydrous ethanol, and crystals were observed under a microscope. Two 50x photos and four 200x photos were captured. Multiple crystals were randomly selected at the 200x photos to measure and calculate their aspect ratios, and their compressive and flexural properties were tested. See Table 2.

[0075] Table 2

[0076]

[0077]

[0078] Figure 2 The electron microscope image of the α-hemihydrate gypsum prepared in Example 2 is shown. It can be seen from the image that the crystal form of the α-hemihydrate gypsum is short columnar and the crystal form is uniform.

[0079] Table 2 shows the properties of α-hemihydrate gypsum prepared in Examples 2 to 12 and Comparative Example 1. From the comparison of Examples 2 to 11, it can be seen that the amount of organic crystal-changing agent added, the pH value of the crystal-changing agent solution, the reaction temperature, and the adjustment of the solid-liquid ratio of the phosphogypsum slurry will affect the aspect ratio and performance of α-hemihydrate gypsum. Comparing Example 2 with Comparative Example 1, it can be seen that the use of the organic crystal-changing agent provided by the present invention can significantly improve the aspect ratio and performance of α-hemihydrate gypsum.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An application of an organic crystal-changing agent, characterized in that: The following steps are involved: The organic crystal-changing agent solution is added to the reactor, and the purified phosphogypsum slurry is added. The mixture is stirred and heated to 120-140 °C. Nitrogen is charged to a pressure of 0.2 MPa in the reactor, and the reaction is carried out for 15-30 minutes. After the reaction is completed, α-hemihydrate gypsum is obtained by filtration and washing. The molecular structure of the organic crystal-changing agent is shown below: ; The amount of the organic crystal-changing agent added is 0.08% to 0.2% of the mass of the phosphogypsum; The pH value of the organic crystal-changing agent solution is 5-9.

2. The use of an organic crystal-changing agent as claimed in claim 1, characterized in that: The preparation method of the organic crystal-changing agent comprises the following steps: Dissolve compound A and compound B in an organic solvent, heat to 45-85°C under nitrogen protection, add compound C, and continue the reaction for 2-4 hours to obtain an organic crystal-transforming agent; Among them, the molecular structure of compound A is shown below: , The molecular structure of compound B is shown below: , The molecular structure of compound C is shown below: 。 3. The use of an organic crystal-changing agent as claimed in claim 2, characterized in that: The molar ratio of compound A, compound B and compound C is 1:(1-5):(0.01-0.09).

4. The use of an organic crystal-changing agent as claimed in claim 2, characterized in that: The method also includes post-treatment, wherein after the reaction is completed, the organic solvent is evaporated, ethyl acetate is added to dissolve, the mixture is washed with water and the layers are separated, and the organic crystal-transforming agent is obtained by concentration.

5. The use of an organic crystal-changing agent as claimed in claim 1, characterized in that: The α-hemihydrate gypsum has a short columnar crystal shape with an aspect ratio of (1.5-2.2):1.